Study on pile-soil contact effect of anti-sliding piles in swelling soil landslides - Xu, Peng; Xing, Xiansen; Jin, Chengcai; Wang, Ruiying; Zhang, Jiabing; Zhang, Xiaohu (Frontiers in Earth Science, 2024)
In recent years, it is not uncommon for swelling soil landslides to occur again after treatment, which has seriously affected the safe operation of highways and railways. The degree of consolidation and cementation of swelling soil is poor, and its fractures are developed and it has a certain expansibility. Under the action of expansion force, its shear strength is obviously reduced. Thus, anti-slide pile support is used to control swelling soil landslides in this study. Based on the geological conditions and genetic mechanism of swelling soil landslide, a three-dimensional geological model with a width of 40 m is established to simulate the interaction mechanism and influencing factors between soil and pile in the process of anti-slip pile support. The results show that the larger the cohesion and internal friction angle, the stronger the soil arch effect, but the sensitivity is higher when the value is small. Therefore, attention should be paid to the weakening effect of soil arch effect in soil with low shear strength. The larger the pile spacing, the less obvious the soil arch effect. The swelling force also has a great influence on the soil arch effect from scratch. With the increase of the expansive force, the soil arch effect is weakened and completely disappears. Therefore, the adverse effects of expansive force should be considered, when designing anti-slide piles in swelling soil areas.